7.2k views
0 votes
Choose the correct simplification of
(a^5b^6)/(a^4b^4)

(a)
a^9b^1^0
(b)
ab^2
(c)
(1)/(ab^2)
(d)
(1)/(a^9b^1^0)

2 Answers

4 votes

Answer:

a^5 - a^4 = a1 or a

b^6 - b^4 = b2

put them together and you get ab^2

I also took the test and got it right

User Dqd
by
5.3k points
6 votes

The correct simplification will be: (b) abĀ²


(a^5 b^6)/(a^4 b^4)

Here we will use the property of exponents for division of two exponential terms with same bases. The original property is :
(x^m)/(x^n) = x^m^-^n

It means if the bases are same , then we will just subtract the exponents while dividing two terms.

Using this property:


(a^5)/(a^4) = a^5^-^4 = a^1 = a

and
(b^6)/(b^4) = b^6^-^4 = b^2

So,
image

User Andy Schweig
by
6.2k points